Global warming's effects on marine and coastal environments: Students' knowledge, attitudes, and environmental behaviour - Dios Sarkity; Adam Fernando; Yudi Pratama; Bony Irawan (Journal of Environment and Sustainability Education, 2025)
Global warming poses serious threats to marine and coastal environments, especially in island and shoreline communities like Kijang Kota in the Riau Islands, Indonesia. Despite the urgency of this issue, research on how students in such vulnerable areas understand and respond to global warming remains limited. This study aims to assess the knowledge, attitudes, and environmental behaviors of junior high school students in Kijang Kota regarding global warming and its effects on the marine and coastal environment. Using a descriptive quantitative approach, data were collected through tests and questionnaires from a sample of 304 students, selected through stratified random sampling. The findings reveal that students’ knowledge was generally low, with an average score placing them in the "poor" category. However, their attitudes toward environmental issues were "very good," reflecting high awareness and concern. In terms of environmental behavior, most students were in the "good" category, showing moderate engagement in eco-friendly actions. The results highlight a gap between students’ strong environmental concern and their limited understanding and actions, pointing to the need for more practical, context-based environmental education in coastal schools. This research offers insights that can help improve climate education and promote more sustainable behavior in island and coastal communities.